Benefits of implementing student-led review and mock examinations in the medical undergraduate gross anatomy curriculum. (2nd September 2022) - Khatskevich, Katsiaryna; Hewitt, Sage T.; Jang, Chang-Woo; Lewis, Nicholas; Liu, Langfeier; McGlawn-McGrane, Britton W.; Bharadwaj, Srinivas Nagaraj; Mhaskar, Rahul
Abstract: Anatomy consists of material that continually defines a student's undergraduate medical curriculum, and thus attaining a solid understanding of it is critical for academic success. Student exposure to anatomy prior to matriculation to the United States (US) medical school is highly variable, with some first introduced to the material in medical school. As a result, students without foundation in anatomy can struggle with adapting to the self-directed learning style that is required to excel with a prosection-based (i.e. hands-off analysis of a cadaver previously dissected by a professional) approach. In this study, second-year US medical students who have previously excelled in the first-year courses at the University of South Florida Morsani College of Medicine (in collaboration with faculty advisors) designed and offered a mock practical examination that mirrors the official practical exam specific to each course: a timed practical examination using dissected human cadavers and radiological imaging to assess anatomical knowledge, followed by a review session. Since the mock practical and review session was designed from a student's perspective, the material could be tailored to specifically address topics that students historically have struggled with. Students who participated in the mock practical and associated review sessions reported feeling more confident than their peers who did not participate. In addition, they significantly outperformed their peers on the official practical examination, independent of any demographic factors or educational background. This study demonstrates the benefits of incorporating peer-assisted learning (PAL) into the anatomical component of the medical school curriculum.